A block coded amplitude clipping and filtering for peak-to-average power ratio in orthogonal frequency ‘division multiplexing system - Yusof, S. K.; Fisal, Norsheila; Kannan, U.; Wong, Y. H. (2003)
One of the major setbacks of Orthogonal Frequency Multipiexing . (OFDM) is its peak-to-average power ratio (PAPR). In this paper, an investigation of block coded amplitude clipping and filtering method to reduce further the PAPR in OFDM system is presented. The BER performance of this method is also analyzed. It is shown through simulation that the block coded amplitude clipping and - filtering method improves the PAPR and BER performance as compared to a block coding technique.